Sonography in obstetrics and gynecology : principles & practice - Fleischer, Arthur C. (New York : McGraw-Hill Medical, 2011)
"Since the publication of the 6th Edition, there have been major new developments and improved understanding of a variety of obstetric and gynecologic disorders. Concomitantly, there have been significant improvements and innovations in sonographic imaging. A few examples of this include 3D/ "live 3D" imaging and more sensitive Doppler techniques. The editors have endeavored to revise and enhance this "Mega-Project" to include both a standard textbook and an associated website containing dynamic studies and up-to-date information on an extensive list of topics. "--Provided by publisher.
Keywords: Ultrasonics in obstetrics; Generative organs, Female -- Ultrasonic imaging; Pregnancy Complications -- ultrasonography; Genital Diseases, Female -- ultrasonography